BUSINESS PLAN OF BUMI KINANTI WEDDING HOUSE - Fatahillah, Fadhli
Wedding houses started to emerge and has been stable in demand in Bogor City. Bumi Kinanti was built in Bogor in 2014 as an ordinary house owned by Mr. Risnandi. However, it was established as a wedding venue in 2017 due to high demand from random people that had been requesting the venue for the wedding ceremony. Then, Bumi Kinanti started to create some strategies to attract its customers. The purpose of this study is to prepare and create a business plan that can be simply applied by Bumi Kinanti. The preparation step of the business plan is started by doing company analysis, market analysis, and competitors analysis which are based on primary research and secondary research, but mostly done with the primary research, The data from the analysis will be used to process a new strategy for the business. The strategy used is cross-selling strategy because it is found to make more profit with the offering of more functionality of the product itself. Bumi kinanti has doing partnership with the former team managment from Andriani cathering which is one of the biggest cathering in Bogor. The list of programs, which planned iii specifically already are the lodging for airbnb or travloka in order to get more brand awareness from people and also get the higher revenue. Also, we offer the event organizer from Bumi Kinanti itself which could make the customer easier to consult their wedding in Bumi Kinanti and it will be more competitive in price. In the marketing, personal selling will be highly focused, since Bumi Kinanti still in the early stage of business. Bumi Kinanti management also plan to make the Booking a lot easier, Bumi Kinanti will more active online, so that people don't need to come to Bumi Kinanti to book the day, since the administrator will be more fast response for online booking. With the help of some stakeholders, the programs were already crafted each month and estimated to gain estimated to gain Rp. 50.800.000,00 for the net profit each month